Stability analysis of networked control systems under DoS attacks in frequency domain via game theory strategy. Issue 14 (26th October 2021) - Cheng, Lingli; Yan, Huaicheng; Zhan, Xisheng; Fan, Sha; Shi, Kaibo
Abstract : In this paper, the stability analysis of networked control systems (NCSs) under Denial-of-Service (DoS) attacks is studied. Firstly, the stability analysis for NCSs free of DoS attacks is investigated. Considering the DoS attacks, the game theory is introduced to establish the non-cooperative game between defender and attacker of NCSs. At the same time, the stability of NCSs is analysed in frequency domain, and the signal-to-noise ratio (SNR) expression is given by using spectral decomposition technique and Nash equilibrium (NE) strategy. The packet dropout phenomenon caused by DoS attacks is described by Bernoulli distribution. By virtue of the NE strategy, the stability of NCSs can be optimised. In the obtained results, the influence of the traditional constraints and DoS attacks is illustrated. Finally, some numerical examples are given to show the effectiveness of the derived theoretical results.